The resilience of integrated agricultural systems to climate change. (15th March 2017) - Gil, Juliana D. B.; Cohn, Avery S.; Duncan, John; Newton, Peter; Vermeulen, Sonja
Abstract : We reviewed studies addressing the extent to which more integrated agricultural systems (IAS) have been found to be more resilient to climate variability and climate change than more specialized agricultural systems. We found limited literature directly addressing the topic, necessitating the use of proxy measures to enlarge the sample. Where necessary, we used agricultural system richness and diversity as proxies for the presence of the sort of synergistic relationships that typify IAS, interannual climate variability for climate change, and myriad agricultural indicators for resilience. We found that (1) 37 papers addressed the topic either through mathematical modeling or statistical modeling; (2) in the statistical papers, integration was overwhelmingly ( n  = 17/24) associated with increased climate resilience; (3) these findings stemmed mainly from comparisons of more versus less diverse or rich farming systems, while few studies investigated the influence of farm system synergies on resilience; (4) yield, revenue, profit, and yield variance were all used to demonstrate resilience; (5) modeling studies tended to investigate resilience across multiple years, while most statistical approaches tracked single‐year outcomes; (6) the IAS‐climate resilience links demonstrated were not generalizable across units of analysis, spatiotemporal scale, and from autonomous to directed integration; and (7) few of the articles reviewed identified and measured the mechanism by which IAS were shown to have conferred resilience. Our findings reveal suggestive, although by no means conclusive, evidence that farm system integration can enhance resilience and highlight the need for research to test whether integration policies can have similar outcomes. WIREs Clim Change 2017, 8:e461. doi: 10.1002/wcc.461 This article is categorized under: Climate Economics > Aggregation Techniques for Impacts and Mitigation Costs Vulnerability and Adaptation to Climate Change > Values‐Based Approach to Vulnerability and Adaptation Abstract : Schematic representation of the resilience of integrated agricultural systems (IAS) to climate change. We found suggestive, though by no means conclusive evidence that farm system integration can enhance resilience to climate change. The vast majority of the studies we reviewed found that, compared to less integrated agricultural systems, more integrated agricultural systems experienced a lesser decline in resilience indicators (e.g. yield, income, yield variance) due to climate shocks and/or exhibit less yield variability under climate variability. The graphic depicts three potential advantages of integration for climate resilience discussed in the reviewed literature: lesser short term shocks, faster recovery from short term shocks, and lesser long term shocks.